Turnskin - Bright, Hannah, author; Candelaria Fletcher, Harrison, advisor; Beachy-Quick, Dan, committee member; Harrow, Del, committee member; Bunn, David, committee member (Colorado State University. Libraries, 2021)
Turnskin is a monstrous exploration in human ferality. A true fairytale about a woman or a wolf or a girl nosing toward the wilderness within the self, it wonders at how to be both human and animal, imagined and real, alive all the way and all at once. Through tender reconciliation of the child and adult self, the project essays toward truth through dream, childscape imagination, the faerie, and the speculative. The story roots in hybridity—of self, genre, form, truth, time and word; and seeks toward Metanonfiction—an inquiry of what a human body can do with a story, and what story does in turn with the mammalian body. Hybridity is enacted in the intersections between poetry and prose at the level of the letter, word, sentence, paragraph, piece, and cohesive sensibility; in pressing the boundaries between what is 'real' and 'fantastical' by blending the conventions and tropes of fairytale and memoir; and in pushing against narrative time and logic through mutual influence of the past, present, and future on one another. Informed by studies in animal science, anthropology, fairytales, poetry, art, and creative nonfiction, the project seeks to expose the sinister implications of what we understand to be real/fixed and imagined/fluid and aspires to converse with the work of Angela Carter, Jenny Boully, Maggie Nelson, Sarah Shun Lien Bynum, Helen Oyeyemi and Lina Maria Ferreira Cabeza-Vanegas, amongst others. In wondering what it means to be a human animal that can both construct our experience out of story and also live it in the nostrils, nerves, pupils of the felt sense, this true story investigates how to unstory—at the level of the tooth, the feather, the bone, what it means to actually makebelieve.
Keywords: body; memoir; story; essay; animal; nonfiction